N2 fixation, grain mineral accumulation, and water-use efficiency in 30 field-grown groundnut (Arachis hypogaea L.) genotypes in Mpumalanga, South Africa, measured using 15N and 13C natural abundance techniques - Ngmenzuma, Titus Y.; Oteng-Frimpong, Richard; Dakora, Felix Dapare (Frontiers in Agronomy, 2025)
African soils are inherently low in mineral nutrients. Incorporating N2-fixing legumes into cropping systems can improve soil fertility and increase crop yields. This study assessed N2 fixation, carbon assimilation, grain mineral accumulation and water-use efficiency of 30 groundnut genotypes grown in the field at the Mpumalanga Province, South Africa, using the 15N and 13C natural abundance techniques. The results revealed marked differences in symbiotic performance between and among the groundnut genotypes, with IS-07273 and ICGV13910 exhibiting greater symbiotic dependency on N2 fixation for their N nutrition and higher amounts of N-fixed. The two high N2-fixing symbioses (IS-07273 and ICGV13910) also accumulated significantly high levels of K, Na, Zn, Cu, Mn, and B in their grain. As a result, there were strong correlations between amounts of N-fixed and K, Na, B, Cu, Zn and Mn for genotype ICGV13910. Genotype IS-07273 also showed significant correlations between N-fixed and S, N concentration (%N) and P, %N and K, as well as nodule number and Ca. As to be expected, genotypes with the highest shoot %N accumulated the most protein in their grain. Out of the 30 groundnut genotypes tested in the field, YENYAWOSO, ICGV13848, ICGV13851, ICGV15033 and ICGV131065 showed greater shoot δ13C values, and hence higher water-use efficiency. The high N2 fixation in genotypes ICGV13910 and IS-07273 correlated positively with macro- and micro-nutrient concentrations in their grain, indicating their potential for use in breeding programmes to enhance nutritional security in groundnut.